Metode Pengaturan Hasil Berdasarkan Jumlah Pohon dalam Pengelolaan Hutan Rakyat pada Tingkat Pemilik Lahan - Yandi, Wahyu Nazri; Muhdin, Muhdin; Suhendang, Endang (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Community forest management are individualized according the decision of the land owners and yet have a standardized manage-ment method. Characteristics of community forest have a high diversity at the level of the land owners. Community forest sustainability can be seen from the forest stand structure. The aim of this study was to obtain horizontal stand structure model and compile yield regulation method for each community forest land ownership. Information of the community forest stand in the Cidokom Vil-lage, Rumpin District obtained exploratively and preparation of the yield regulation method analyzed descriptively.  Sample of sub-districts, villages, and community forest owners was determined by purposive sampling by considering the potential of community forests, technical convenience in the field, accessibility of research locations, and representation of land area data in community forest land ownership groups. From negative exponential function at community forest, obtained “k” values ranges between 39.71–2318.99 and “a” values ranges between -1.58–0.01. The results showed that the stand structure of each land owners of community forest varies and yield regulation method can be used by the community forest landowners which can be adjusted with the cutting decision and land contition to achieve community forest sustainability.